Immunohistochemical hENT1 expression as a prognostic biomarker in patients with resected pancreatic ductal adenocarcinoma undergoing adjuvant gemcitabine-based chemotherapy. Issue 4 (15th February 2017) - Bird, N T E; Elmasry, M; Jones, R; Psarelli, E; Dodd, J; Malik, H; Greenhalf, W; Kitteringham, N; Ghaneh, P; Neoptolemos, J P; Palmer, D
Abstract: Background: Human equilibrative nucleoside transporters (hENTs) are transmembranous proteins that facilitate the uptake of nucleosides and nucleoside analogues, such as gemcitabine, into the cell. The abundance of hENT1 transporters in resected pancreatic ductal adenocarcinoma (PDAC) might make hENT1 a potential biomarker of response to adjuvant chemotherapy. The aim of this study was to see whether hENT1 expression, as determined by immunohistochemistry, was a suitable predictive marker for subsequent treatment with gemcitabine-based adjuvant chemotherapy. Methods: A systematic review was performed, searching databases from January 1997 to January 2016. Articles pertaining to hENT1 immunohistochemical analysis in resected PDAC specimens from patients who subsequently underwent adjuvant gemcitabine-based chemotherapy were identified. Eligible studies were required to contain survival data, reporting specifically overall survival (OS) and disease-free survival (DFS) with associated hazard ratios (HRs) stratified by hENT1 status. Results: Of 42 articles reviewed, eight were suitable for review, with seven selected for quantitative meta-analysis. The total number of patients included in the meta-analysis was 770 (405 hENT1-negative, 365 hENT1-positive). Immunohistochemically detected hENT1 expression was significantly associated with both prolonged DFS (HR 0·58, 95 per cent c.i. 0·42 to 0·79) and OS (HR 0·52, 0·38 to 0·72) in patients receiving adjuvant gemcitabine but not those having fluoropyrimidine-based adjuvant therapy. Conclusion: Expression of hENT1 is a suitable prognostic biomarker in patients undergoing adjuvant gemcitabine-based chemotherapy. Abstract : Standardization needed to see if it's really useful